2021
DOI: 10.4251/wjgo.v13.i9.980
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of integrin-activating peptides derived from tenascin-C in colon cancer progression

Abstract: Tenascin-C (TNC) is an adhesion modulatory protein present in the extracellular matrix that is highly expressed in several malignancies, including colon cancer. Although TNC is considered a negative prognostic factor for cancer patients, the substantial role of the TNC molecule in colorectal carcinogenesis and its malignant progression is poorly understood. We previously found that TNC has a cryptic functional site and that a TNC peptide containing this site, termed TNIIIA2, can potently and persistently activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 119 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…These fragments in turn can regulate a wide array of biological processes, including angiogenesis, cell migration, adhesion and differentiation as well as tumor growth and metastasis [ 323 ]. It was found that matrikines can originate from collagen [ 324 , 325 ], elastin [ 326 , 327 ], tenascin [ 328 , 329 ], fibronectin [ 330 , 331 ], laminins [ 332 ], decorin, thrombospondin and versican [ 333 ].…”
Section: Degradation Of the Tumourigenic Matrixmentioning
confidence: 99%
“…These fragments in turn can regulate a wide array of biological processes, including angiogenesis, cell migration, adhesion and differentiation as well as tumor growth and metastasis [ 323 ]. It was found that matrikines can originate from collagen [ 324 , 325 ], elastin [ 326 , 327 ], tenascin [ 328 , 329 ], fibronectin [ 330 , 331 ], laminins [ 332 ], decorin, thrombospondin and versican [ 333 ].…”
Section: Degradation Of the Tumourigenic Matrixmentioning
confidence: 99%
“…It can provide a permissive environment for cancer cells to move through the ECM and invade surrounding tissues. TNC has also been associated with epithelial-mesenchymal transition (EMT), a process linked to increased cancer cell motility and invasiveness [ 50 ]. The ELK3 gene, also known as NET (Nuclear Protein Related to SAM Pointed Domain-Containing ETS Transcription Factor), has been found to play roles in cancer development and progression [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variants containing FNIII A1A2 repeats also inhibit T cell activation in vitro, suggesting that TNC exerts immunosuppressive activity [ 151 ]. Additionally, work from our laboratory has shown that TNC harbors a functional cryptic site that comprises the YTITIRGV amino acid sequence located in the FN type III A2 repeat, and fragments containing this sequence, termed TNIIIA2 peptide, can potently enhance cell adhesion by activating β1-integrins; this activation state is sustained for an extended period [ 152 ]. Based on these functions, TNIIIA2 contributes to the ability of cancer cells to acquire malignant properties, including hyper-proliferation, disseminative migration, anchorage-independent growth, and anoikis resistance [ 153 , 154 , 155 , 156 , 157 ].…”
Section: Matricellular Proteins In Cellular Senescencementioning
confidence: 99%